THE INFLUENCE OF WORK DISCIPLINE, JOB TRAINING AND INCENTIVES ON EMPLOYEE PERFORMANCE - Muhammad Rizqi Zati; Syardiansah Syardiansah; Juliana Dewi Sri Wahyuni (UNIVERSITAS PGRI MADIUN, 2024)
Abstract:This study sought to ascertain how incentives, job training, and work discipline affected the performance of PERUMDA Water Drinking Tirta Tamiang staff. 43 PERUMDA Water Drinking Tirta Tamiang permanent employees form the saturated sample for this study. Multiple linear regression analysis and the traditional assumption test were utilized in the data analysis approach. The coefficient of determination test, t test, and F test were then employed as a proof of hypothesis. According to the results of the coefficient of determination test, 59.2% of the performance factors of the PERUMDA Air Drinking Tirta Tamiang employees may be explained by work discipline, job training, and incentives, while 40.8% can be impacted by other variables not included in this study. The outcomes of the The t-test results demonstrate that work discipline, job training, and incentives all significantly affect how well PERUMDA Water Drinking Tirta Tamiang personnel perform. The f test results show that incentives, job training, and work discipline all have a major impact on how well employees perform at PERUMDA Water Drinking Tirta Tamiang.Keywords: Work Discipline, Job Training, Incentives and Performance